Local Memory Search Bat Algorithm for Grey Economic Dynamic System - Mo Yuanbin; Zhao Xinquan; Xiang Shujian (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Control system is a pattern for describing microeconomic performance, so it can provide theory basis for policy-making to make economic performance well and continuously by analyzing and solving the model of economic control system. After analyzing the characteristics of Bat Algorithm (BA), the method to adjust each step of BA is proposed. In the method, each bat took advantage of the optimal location that it had found to guide the direction of search. The result of the case study showed that the proposed algorithm was efficient, then the proposed algorithm was used to solve the grey economic dynamic system, and the results further showed that the method was valid for solving economic control problems. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.3149